The Reliability and Validity of the Japanese Version of the Modified Dental Anxiety Scale among Dental Outpatients - Mika Ogawa; Teppei Sago; Hirokazu Furukawa (The Scientific World Journal)
Introduction. A careful assessment of dental anxiety is necessary for its management. The Modified Dental Anxiety Scale (MDAS) is one of the most commonly used questionnaires to measure dental anxiety in the world. The reliability and validity of the Japanese version of MDAS have been demonstrated using undergraduates and a few patients with dental anxiety. The aim of the present study was to examine the reliability and validity of the Japanese version of the MDAS using a wide range of age samples in dental clinics. Methods. A total of 275 outpatients (145 men and 130 women; 21–87 years) from two dental clinics participated in the present study. Dental anxiety was assessed using the Japanese version of the MDAS and the Dental Fear Survey (DFS). The psychometric evaluation included exploratory factor analysis, and Cronbach’s α was used to evaluate for internal consistency. Criterion validity was assessed by correlating the MDAS and DFS scores using Spearman’s correlation coefficient. validity was evaluated by examining related factors’ differences in the MDAS score (e.g., sex and negative dental experiences). Results. Six patients (2.2%) reported high levels of dental anxiety (MDAS score ≥ 19). The internal consistency of the MDAS score was high (Cronbach’s α = 0.88). Dental anxiety was significantly higher among women (P=0.007), in patients with previous negative dental experiences (P<0.001), and among those with lower frequencies of dental visits (P<0.001). The MDAS score was significant and related to age (r = 0.48) and the DFS score (r = 0.87). Factor analysis revealed all items measured only one construct. Conclusions. The Japanese version of the MDAS score was found to be a reliable and valid measure of dental anxiety among dental outpatients. It could be useful for the Japanese dental practitioner to measure dental anxiety in a clinical setting.